2005
DOI: 10.1016/j.trstmh.2003.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a malaria intervention strategy using knowledge, practices and coverage surveys in rural Bolifamba, southwest Cameroon

Abstract: We evaluated the impact of a malaria intervention in Bolifamba in rural Cameroon. The intervention consisted of educating the community on management of malaria and provision of a dispensary for early diagnosis and treatment. In July 2001, prior to the intervention, a questionnaire was used to obtain information on knowledge of and practices toward childhood malaria of 185 mothers of children aged 0-5 years. The same questionnaire was administered to 120 of the 185 mothers, one-year post-intervention. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 9 publications
6
51
0
Order By: Relevance
“…11 So, attention must be paid to educate the community on malaria signs and symptoms; Along with our study, other studies have established that the knowledge of signs and symptoms plays a particular role on early diagnosis and treatment. 21 Gender identities, status, roles and responsibilities influence vulnerability to disease, access to health care and the impact of disease for women, men, girls and boys. 22 The social consequences of infectious disease are often more severe for women than for men and illness imposes a particularly heavy labour burden upon women.…”
Section: Population Movements and Malariamentioning
confidence: 99%
“…11 So, attention must be paid to educate the community on malaria signs and symptoms; Along with our study, other studies have established that the knowledge of signs and symptoms plays a particular role on early diagnosis and treatment. 21 Gender identities, status, roles and responsibilities influence vulnerability to disease, access to health care and the impact of disease for women, men, girls and boys. 22 The social consequences of infectious disease are often more severe for women than for men and illness imposes a particularly heavy labour burden upon women.…”
Section: Population Movements and Malariamentioning
confidence: 99%
“…Access to free diagnoses and treatments have been shown to be a major determinant in malaria control [10] and despite some evidence, many countries still rely on user fees for financing healthcare [11].…”
Section: Contextmentioning
confidence: 99%
“…Educating users alone does appear to be effective at changing their knowledge of the appropriate anti-malarial or dosage; 24,26,37 however, it has been frequently shown elsewhere that changes in knowledge do not necessarily correlate with changes in behavior. 38,39 The impact on actual behavior was only measured in one study, 19 and this showed significant effects for the use of correct AM (49% in the intervention area, compared with 30% in the nonintervention area); there was no significant difference between intervention and comparison areas for using the correct dose.…”
Section: Measurement Of Individual Components Of Effective Treatment mentioning
confidence: 99%